2015
DOI: 10.1186/s12906-015-0608-5
|View full text |Cite
|
Sign up to set email alerts
|

A survey of the availability in Canadian pharmacy chains of over-the-counter natural health products for menopause symptoms

Abstract: BackgroundMenopause is a natural phase in a woman’s aging process, characterized by the cessation of menstruation. Women who are going through the menopause transition can experience physiological symptoms that significantly impact their quality of life. Concern about adverse effects of traditional hormone therapy often leads women to purchase over-the-counter (OTC) natural health products (NHPs). The goal of this study was toinvestigate the range of OTC NHPs for menopause available to Canadian women, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Since that time, postmenopausal women and healthcare workers have been searching for an alternative therapy. A Canadian study has shown that many postmenopausal women consider the use of complementary or alternative medicine (CAM) for alleviating menopausal syndrome yet have concerns regarding its cost and efficacy [ 9 ]. Most women using CAM chose not to inform their physicians because they felt physicians were not good enough for judging the effects of CAM [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since that time, postmenopausal women and healthcare workers have been searching for an alternative therapy. A Canadian study has shown that many postmenopausal women consider the use of complementary or alternative medicine (CAM) for alleviating menopausal syndrome yet have concerns regarding its cost and efficacy [ 9 ]. Most women using CAM chose not to inform their physicians because they felt physicians were not good enough for judging the effects of CAM [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since then, healthcare professionals and women have been seeking alternative therapies. In Canada for example, it has been found that 60% to 90% of women would consider taking complementary and/or alternative medicine (CAM) for menopausal symptoms, but are concerned about the efficacy and cost [2]. Many patients taking CAM choose not to tell their doctors because they feel doctors are not knowledgeable enough or are biased against CAM [3].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, to mitigate further consumer confusion, harmonisation of evidence required for health claims between food and dietary supplements should also be investigated. In some jurisdictions, such as Canada, standards of evidence for claims on natural health products have undergone considerable scrutiny (15,16) . Unfortunately, unlike the food industry, criticism in the supplement industry extends beyond the context provided in claim wording and stems from concerns over a lack of efficacy to support reported claims and the absence of bioactive ingredients that are reported on ingredient lists.…”
mentioning
confidence: 99%